Empowering Ginger Farmer Through Fostering the Production of Liquid Organic Fertilizer During the Covid-19 Pandemic - Slamet Fauzi; Susan Barbara Patricia (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
COVID-19 pandemic had several detrimental effects on the world’s economy and people around the world. Ginger farmers in Genteng Kulon village, Banyuwangi Regency, are one of the communities affected by COVID-19. Since COVID-19 came, the price of chemical fertilizers has remained expensive, and the price of ginger is very high, up to IDR 90.000 per kg, so ginger farmers need a new affordable alternative fertilizer. Fostering the manufacture of liquid organic fertilizer from banana stem waste is the right option to help ginger farmers meet their fertilizer needs and make it efficient in using available waste. The method used in this community development was through the Community Service Program consisting of various activities: training on the production of liquid organic fertilizer; packaging; labeling; and application to ginger plants. The success of this program was evidenced by the level of farmers’ understanding of the procedure being taught, which was assessed using a questionnaire. The results showed that the farmers’ understanding of the material being taught significantly increased as compared with that before they were educated. The percentages of average understanding of the training material for liquid organic fertilizer, packaging, labeling, and application were 75%, 80%, 80%, and 85% respectively. These numbers were very different from those representing the farmers’ knowledge before the training. These average percentages were 15.5%, 14%, 16.5%, and 11.5%. Therefore, this program was successful in providing new knowledge to farmers in the production of liquid organic fertilizer.